Pengaruh Literasi Keuangan, Akses Permodalan Dan Penggunaan Fintech Terhadap Kinerja Umkm Di Kota Batu Pada Masa Pandemi Covid-19 - Diana Putri Oktarini; Jeni Susyanti; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThe purpose of this study was to determine and analyze financial literacy, access to capital and the use of Fintech on the performance of MSMEs in Batu City during the COVID-19 pandemic. The type of research used in this research is explanatory research with a quantitative approach. The data sources used in this research are primary and secondary data. The population used in this study was 93 MSME actors in Batu City, the culinary sub-sector based on data from the Batu City PLUT in 2021. The sampling technique used in this study was Non-probability sampling with a census/total sampling technique. So that all the population in this study becomes the sample that will be used. The results of this study indicate that partially the financial literacy variable affects the performance of MSMEs, the access to capital variable does not affect the performance of MSMEs, and the variable use of FinTech affects the performance of MSMEs. Keyword : Access to Capital, Financial Literacy, MSME Performance, Use of Fintech